Can Patients Be Transplanted or Undergo Ventricular Assist Device Placement During the COVID-19 Pandemic? Padova Perspective. Issue 4 (18th January 2021) - Bagozzi, Lorenzo; Bottio, Tomaso; Tarzia, Vincenzo; D'Onofrio, Augusto; Gambino, Antonio; Bianco, Roberto; Toscano, Giuseppe; Gerosa, Gino
Abstract : The SARS-CoV-2 pandemic is nowadays an international emergency and the North-Italian regions have faced a high rate of infection and case fatality. A logistic and structural rearrangement has been required to ensure COVID-19-free areas, to save human and economic resources, and to solve all incoming urgencies. Herein, we report the Padova experience in heart transplantation and mechanical circulatory support implantation for severe INTERMACS class patients with satisfactory results during COVID-19 pandemic.